Assess the Status of Plastic Waste Generation in Phu Tho Province and Solutions - Anh, Pham Lan; Tue, Nguyen Tai; Dung, Luu Viet; Quy, Tran Dang; Nhuan, Mai Trong; Hung, Luu Viet (VNU Journal of Science: Earth and Environmental Sciences, 2024)
The status of plastic waste (PW) generation from household solid wastes (HSW) in Phu Tho province is assessed using the waste flow model. Results show that the average percentage of PW in HSW in Phu Tho province is 12%. In 2022, the amount of PW generated in Phu Tho province is 91.7 tons/day, of which urban areas account for about 29% and rural areas account for 71%. The average amount of PW generation in urban areas is 32.9 kg/person/year and in rural areas is 19.5 kg/person/year. The amount of PW collected in 2022 is 74.6 tons/day, of which urban and rural areas is 25.5 tons/day and 49.1 tons/day, respectively. The amount of PW classified for recycling is 28 tons/day, corresponding to 31% of the amount of PW generated. The amount of PW discarded into the environment and into the water environment specifically is estimated to be 24.6 tons/day and 2.3 tons/day, respectively. It is forecasted that by 2030 the amount of PW generated will be about 129 tons/day, equivalent to 47,085 tons/year. The main causes of the increase in the amount of PW generated include the ineffective classification of HSW, the lack of human resources , and the ineffective management policies. To reduce PW, it is necessary to synchronously implement solutions on classification, collection, transportation , and treatment of HSW , raise people's awareness about limiting and not using single-use plastic items and plastic bags; and increase reus ing and recycling of PW.